The Effect of Using Figurative Language on the Reading Comprehension of First Secondary EFL Students in Jordan - Al-Omari, Hamzah; Abu-Hamdieh, Sumayyah (Jordan Journal of Educational Sciences, 2006)
The purpose of this study was to investigate the effect of using figurative language on the reading comprehension of first secondary EFL students. The sample of the study consisted of 75 students at The Arab Model Schools in Amman. Six different reading passages were taught to the experimental and the control groups for two months. Data were analyzed using means, standard deviations and ANCOVA. The results of the study showed there were statistically significant differences (α=0.05) in the total reading comprehension, the literal reading comprehension, and the analytic reading comprehension of students. Those differences were in favor of students in the experimental group. As for the evaluative level, there were no statistically significant differences. Based on these results, the researchers recommended that there should be more emphasis on incorporating and teaching figurative language in order to facilitate reading comprehension.